Diagnostic Study on Identification Method of Enterobacteriaceae Directly from Blood Culture - Ciptaningtyas, V. Rizke; Hapsari, Rebriarina; Kristina, Tri Nur; Winarto, Winarto (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2015)
Introduction: The provision of rapid diagnosis results from positive blood cultures is important for clinical management of sepsis. Using conventional method as a reference method in laboratory, time needed for bacterial identification are 24 hours longer because it has to deal with primary isolation step. Objectives: This study investigated the accuracy of direct inoculation technique of bacteria from positive blood culture vials to biochemical test tubes without primary isolation step to identify Enterobacteriaceae, second most common causative agent of sepsis.Methods: The study was conducted at the Microbiology Laboratory Medical Faculty of Diponegoro University. This is a diagnostic study. As the study sample, blood cultures in BACTEC bottles from Dr. Kariadi General Hospital Semarang with bacterial growth in it. Inclusion criteria was Gram-negative rod bacteri, staining results from BACTEC blood culture bottles, and as a exclusion criteria, there are more than one colony found on blood agar and Mac Conkey agar and showed positive result in oxidation test. Identification of bacteria based on biochemical table of Enterobacteriaceae. Data were analyzed with a 2x2 table.Results: Thirty two samples included in this study. Ten samples (31%) were excluded. Twenty one from twenty two (95%) study samples accurately identified to the genus level by direct inoculation method.Conclusion: The results showed that the direct inoculation method provides an acceptable genus identification, with a potential saving of 24 hours compared with conventional methods.